The Influence of Trust, Intellectuality, and Leadership Style on The Openness of Leaders in Islamic Educational Institutions - Putra Jaya, Doris; Ali, Hapzi (International Journal of Advanced Multidisciplinary, 2023)
Every organization desires an open leader but the openness of the leader cannot just happen there are many factors that can influence it among these factors are those revealed in this article such as the influence of trust in subordinates, intellectuality of the leader, and his leadership style. This research is a literature study with a type of descriptive qualitative research with library research that seeks to describe the factors that influence the openness of leaders. This study aims to provide an analysis of the factors that can affect the openness of leaders obtained from the results of literature review or literature study by comparing various written sources such as articles, journals and books that are relevant to the study in this study.